Difficulties facing Use of Learning Cycle Method (5e's) Strategy, and the Suggestion to their Application from the Science Teachers point of view - A Field Study in the Second Cycle of the Basic Education Schools in Lattakia City - منصور, ندى; ابراهيم , جمعة (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of the research is to identify the difficulties facing use of learning cycle method and the suggestion to their application, and the suggestion to their application from the science teachers point of view (5e's) strategy from the science teachers point of view in the second cycle of the basic education schools in Lattakia City. The descriptive approach was adopted, and a questionnaire consisting of (46) phrases was used, it is divided into five areas: (difficulties related to academic content, difficulties related to learning time, difficulties related to teachers, difficulties related to the educational environment, difficulties related to students), and an open question about the sample members’ suggestions for implementing the Learning Cycle Method (5e's), the questionnaire was applied to a sample of (122) science teachers in the schools of the second cycle of basic education in the city of Lattakia for the academic year 2021/2022. Among the most important findings of the research: The difficulties of using the strategy of the Learning Cycle Method (5e's) from the point of view of science teachers in the schoolsof the second cycle of basic education in the city of Lattakia came to a high degree. Among the most important proposals of science teachers to implement the strategy of the of the Learning Cycle Method: developing model lessons on the application of the strategy of the Learning Cycle Method, and holding continuous workshops for teachers on the use of modern teaching strategies. There are statistically significant differences between the answers of the research sample of science teachers in the schools of the second cycle of basic education in the city of Lattakia about the difficultiesof using the strategy of the Learning Cycle Methodaccording to the variable of scientific and educational qualification in favor of the educational qualification diploma holders, and according to the variable of training courses in favor of Teachers who have followed training courses.